Vultures in Courts: Why the UNCTAD Principles on Responsible Financing Cannot Stop Litigation. (30th October 2015) - MEGLIANI, MAURO
Abstract: The decision of the US Supreme Court rendered in NML v. Argentina has enabled the vulture funds to enforce in full their claims against the payments to be made by Argentina in favour of those holders who had tendered their bonds under a previous exchange offer. This scenario may have a disruptive impact on the functioning of the financial markets and endanger the restructuring processes of sovereign debt. The race to the courts by the vulture funds could be stopped under the UNCTAD Principles on Responsible Financing where the behaviour of those creditors who acquire debt instruments of sovereigns in distress and remain aloof from a restructuring to secure preferential treatment is marked as abusive. Unfortunately, so far the legal status of this abusive behaviour is unable to overturn the interpretation of the pari passu clause under New York law given by the US Federal Courts which stands at the base of the problem. To overcome this impasse the suggestion is to insert in the UN proposal of a multilateral legal framework for sovereign restructuring processes a specific provision qualifying as overriding a mandatory restructuring plan approved through a certain quorum which has received certification by the IMF. This qualification would serve the purpose of applying the plan to all creditors, and not just to those who register under the process. Moreover, this qualification would be considered as part of the public policy of the states participating to the UN proposal so as to block the enforcement of judgments rendered in non-participating fora.